A nexus of natural resource rents, institutional quality, human capital, and financial development in resource-rich high-income economies. (December 2021) - Hussain, Muzzammil; Ye, Zhiwei; Bashir, Adnan; Chaudhry, Naveed Iqbal; Zhao, Yingjun
Abstract: Sustainable development is a preferred goal for every economy. For sustainable development, the role of natural resources is substantially debated in the literature, but the studies on human capital, innovation, and institutions are uncommon. Therefore, this study is designed to re-visit the resource-curse hypothesis by recruiting human capital, innovation, and institutional quality in 23 resource-rich high-income economies. To estimate the linkage of the above-stated hypothesis, the dynamic common correlated effect estimator/cross-sectional autoregressive distributive lag (CS-ARDL), augmented mean group (AMG), and common correlated effect mean group (CCE-MG) estimators are used. Findings suggest the resources as blessings, human capital promotes financial development (FD), and institutional quality (IQ) is also supportive towards financial development in high-income resource-rich economies. It refers to the efficient use of natural and human resources to achieve development goals by high-income countries in the presence of technological innovation. Findings are also robust to the policy suggestions. Highlights: The resource-curse hypothesis is revisited in 23 high-income resource-rich countries. The role of institutional quality, human capital, and technological innovation is studied for financial development. Second-generation econometric techniques are applied i. e. CIPS unit root test Westerlund Co-integration, CS-ARDL, AMG, and CCEMG. Findings reflect the resources as blessings.